Outage Probability Analysis of Multiple-Antenna NOMA over Generalized-K Channels - Altin, Gokhan; Gucluoglu, Tansal (IEEE, 2022)
Due to its spectral efficiency, Non-Orthogonal Multiple Access (NOMA) is a promising approach for 6G and beyond communication systems. Therefore, the success of next-generation communication techniques using NOMA in more realistic environments needs to be examined. The generalized-K channel model has just started to be used in the literature since it can realistically model a wide range of the fading and shadowing effects of the channel. In this paper, outage probability analysis of multi-antenna NOMA technique over generalized-K channels is performed and a closed form solution is presented and verified by computer simulations.
Keywords: Multiple-antenna systems; NOMA; outage probability; generalized-K fading channels; ACCESS; PERFORMANCE; CHALLENGES; Telecommunications